PENGARUH NILAI PRODUK, HARGA DAN CITRA MEREK TERHADAP NIAT BELI ULANG MELALUI SIKAP PELANGGAN PENGGUNA SMARTPHONE SAMSUNG (Studi Pada Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Stikubank Semarang) - Decidiana Natalia Neno, 12.05.51.0192 (Students Journal of Economic and Management, 2016)
The aim of this study is to analyze the effect of product value, price, and brand image against the re-purchase intention through the customer attitudes of Samsung smartphone users. The respondents are 54 students from the Faculty of Economics and Business who want and ever bought a Samsung smartphone. The sampling technique used is purposive sampling, and the analization used is multiple linear regression. The data which have been analyzed from the questionnaire, then are continued to be tested with a validity test, reliability test, hypothesis, and regression. In result, the variable of product value, price, and brand image influence the customer attitudes. Together, the product value, price, brand image and customer attitudes give influence to the re-purchase intentions on Samsung smartphone. The final conclusion of this study can be recommended as a suggestion for the management. The researcher believes that the approach through the product value, price and brand image will affect to the confidence and the evaluation of the customer attitudes that will raise up the re-purchase intention of the smartphone Samsung. The limitation of this study is the sampling period that relative short and the limitation of population which only investigate in the scope of the Faculty of Economics and Business, University of Stikubank. Therefore, further studies are suggested to consider the time in the sampling period and extend the range of the sample population in order to obtain a more complete data and information. Keywords: product value, price, brand image, customer attitudes and re-purchase intention